2022
DOI: 10.3389/fimmu.2022.878457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of a CD3/CD8-Based Immunoscore in Neuroblastoma Patients Using Digital Pathology

Abstract: BackgroundInfiltrating immune cells have been reported as prognostic markers in many cancer types. We aimed to evaluate the prognostic role of tumor-infiltrating lymphocytes, namely CD3+ T cells, CD8+ cytotoxic T cells and memory T cells (CD45RO+), in neuroblastoma.Patients and MethodsImmunohistochemistry was used to determine the expression of CD3, CD8 and CD45RO in the tumor samples of 244 neuroblastoma patients. We then used digital pathology to calculate the densities of these markers and derived an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The density of positive staining for CD20 and CD138 was digitally quantified as the number of positive cells per square millimeter (mm 2 ), as described in detail in our previous studies [ 5 , 18 ]. Briefly, all pathological slides were scanned at 200x magnification (Pannaromic Scan 150, 3DHistech, Hungary) and autoexamined by digital analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of positive staining for CD20 and CD138 was digitally quantified as the number of positive cells per square millimeter (mm 2 ), as described in detail in our previous studies [ 5 , 18 ]. Briefly, all pathological slides were scanned at 200x magnification (Pannaromic Scan 150, 3DHistech, Hungary) and autoexamined by digital analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a comprehensive understanding of tumor-infiltrating lymphocytes (TILs) is crucial for overcoming the challenges and opportunities associated with additional immunotherapy against NB. Several studies have shown that TIL subtypes include B and T cells, macrophages, and natural killer (NK) cells [ [5] , [6] , [7] ]. Tumor-infiltrating T cells are known to be involved in antitumor immunity, and cytotoxic CD8 + T cells, which have been widely investigated in cancers, control tumor growth and metastasis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…GM‐CSF signaling activates anti‐tumor response of some eosinophils in mice, although this effect has not been specifically observed with neuroblastoma 66–68 . Notably for neuroblastoma tumorigenesis, DC1 induction 48,49 and CD8+ T cell antitumor immunity promotion 50 by GM‐CSF (Table 2) may be especially important because neuroblastoma cells potently inhibit dendritic cell generation, migration and function, 76–78 and a higher risk of progression and death has been correlated to low CD8+ and other T cell numbers in patients with neuroblastoma 79 …”
Section: Gm‐csf In Combination With Anti‐gd2 Monoclonal Antibodiesmentioning
confidence: 99%